2002
DOI: 10.1093/jnci/94.19.1469
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Benefits of Different Strategies to Screen for Cervical Cancer in Less-Developed Countries

Abstract: Well-organized screening programs can reduce cervical cancer mortality in less-developed countries at low costs. These cost-effectiveness data can enhance decision-making about optimal policies for a given setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
125
1
8

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 86 publications
5
125
1
8
Order By: Relevance
“…Mandelblatt et al in Thailand modeled three strategies including; VIA, HPV DNA testing, and Pap smears and concluded that VIA with immediate treatment for women aged 35-55 years was the most cost-effective strategy (Mandelblatt et al, 2002a). Sroczynski et al conducted a study in Germany and reported that HPV DNA testing alone every two years starting at age 30 was the most costeffective strategy.…”
Section: Comparison Of Starting Age Of Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandelblatt et al in Thailand modeled three strategies including; VIA, HPV DNA testing, and Pap smears and concluded that VIA with immediate treatment for women aged 35-55 years was the most cost-effective strategy (Mandelblatt et al, 2002a). Sroczynski et al conducted a study in Germany and reported that HPV DNA testing alone every two years starting at age 30 was the most costeffective strategy.…”
Section: Comparison Of Starting Age Of Screeningmentioning
confidence: 99%
“…Four articles in four high income countries (Goldie et al, 2001;2004;Mandelblatt et al, 2002a;Bistoletti et al, 2008;Burger et al, 2012;de Kok et al, 2012), nine middle income countries from seven articles Andres-Gamboa et al, 2008;Vijayaraghavan et al, 2009;Chow et al, 2010;Levin et al, 2010) and 1 article in low income countries suggested starting age after age 30 (Table 1).…”
Section: Comparison Of Starting Age Of Screeningmentioning
confidence: 99%
“…Because VIA requires less infrastructure, training, equipment, and specialized personnel than other cervical cancer screening methods, it is well suited to low resource settings. A series of studies has demonstrated its effectiveness (Megevand et al, 1996;Belinson et al, 1999; University of Zimbabwe and Jhpiego, 1999;Mandelblatt et al, 2002;Goldie et al, 2005;Sankaranarayanan et al, 2005Almonte et al, 2007), and over 40 low-income countries have introduced VIA on either a national or pilot-study basis (CCA, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…46 By contrast, studies using liquid based cytology and HPV DNA testing have reported costs from 121 USD to 184,000 USD per life year saved or per quality-adjusted life-year (QALY). [11][12][13][14][15][16][17][18][19][20][21][22] Possible reasons for discrepancies include the fact that we did not include screening of young women in our model, the setting with organized screening, the setting with midwives (who have lower salaries than doctors) for taking smears, population-based real-life input data and analysis using a probabilistic state transition model.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Several studies have evaluated the economic impact of cervical screening with and without HPV testing, but have reported variable results. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Possible reasons for discrepancies include different modeling methodologies, use of surrogate endpoints and use of input data based on clinical studies that may not have been representative of the population as a whole. However, most modeling studies have consistently found similar reductions of the cumulative lifetime risk of invasive cervical cancer as a result of cytology and HPV DNA screening.…”
mentioning
confidence: 99%